Upacara Kematian Sebagai Sarana Pemberitaan Kabar Sukacita - Fatony Pranoto; Ivonne Eliawaty; Surja Permana (Jurnal Teologi dan Pelayanan Kerusso, 2019)
Normally, death means a cessation of life in all its forms. In terms of humans, that means the cessation of one's life. When the time comes, the spirit separated from the human body. All human pride has vanished. However, to deliver the dead to the last house, many people will gather there. This is an opportunity to be able to preach the good news to the living, that there is life after death. It is not finished here. The preacher needs to prepare to explain it about the good news. So that, this opportunity can bring people to salvation in the Lord Jesus Christ.